2005
DOI: 10.1037/0735-7044.119.3.821
|View full text |Cite
|
Sign up to set email alerts
|

The Serotonergic Agonists Quipazine, CGS-12066A, and α-Methylserotonin Alter Motor Activity and Induce Hindlimb Stepping in the Intact and Spinal Rat Fetus.

Abstract: The effects of serotonergic agonists were examined in intact and spinal fetuses, using an in vivo fetal rat preparation. On Gestational Day 20, fetuses were prepared with a midthoracic or sham spinal transection. Dose-response curves were obtained for quipazine (nonselective 5-hydroxytryptamine [5-HT] agonist; 1.0-10.0 mg/kg), CGS-12066A (5-HT-sub(1B) agonist; 1.0-30.0 mg/kg), and alpha-methylserotonin (alpha-Me-5-HT; 5-HT-sub-2 agonist; 0.2-15.0 mg/kg). During a 10-min test, each of the agonists (delivered vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 58 publications
3
66
0
Order By: Relevance
“…At the time of M6 formation, quipazine, a nonselective 5-HT agonist, was released. The pharmacological activity was much lower than that of TZB-30878 (Brumley and Robinson, 2005). One of the major metabolic pathways was caused by formation of the cyclic metabolite M6 via intermediates M7 and M8.…”
Section: Biotransformation Of Tzb-30878mentioning
confidence: 99%
“…At the time of M6 formation, quipazine, a nonselective 5-HT agonist, was released. The pharmacological activity was much lower than that of TZB-30878 (Brumley and Robinson, 2005). One of the major metabolic pathways was caused by formation of the cyclic metabolite M6 via intermediates M7 and M8.…”
Section: Biotransformation Of Tzb-30878mentioning
confidence: 99%
“…Essentially all pharmacological agents undergo transplacental drug transfer (Benitz & Druzin, 2005;Nau & Plonait, 1998), including general anesthetics that can induce varying degrees of fetal anesthesia and behavioral depression (Ostheimer, 1984). Ether is relatively inexpensive, readily available, and easy to administer, and therefore continues to be the most commonly used maternal anesthetic in psychobiological investigations of perinatal rats (Brumley & Robinson, 2005;Kleven, Lane, & Robinson, 2004;Kozlov, Petrov, Varlinskaya, & Spear, 2006;Petrov, Nizhnikov, Varlinskaya, & Spear, 2006;Robinson, 2005;Smotherman, 2002Smotherman, , 2003. Ether, however, is characterized by high blood solubility that can be associated with accumulation in the fetal blood and tissues, and altered neurobehavioral function (Hodgkinson, Marx, Kim, & Miclat, 1977;Palahniuk, Scatliff, Biehl, Wiebe, & Sankaran, 1977).…”
Section: Introductionmentioning
confidence: 98%
“…Since its primary production is in the raphe nucleus in the brain, post SCI the level of serotonin decrease drastically in the spinal cord caudal to the lesion. It has been previously observed that pharmacological treatment with the drug quipazine can facilitate stepping in animals whose spinal cords have been completely severed [5][6][7]. In addition, we have shown previously that the level of recovery is greater when robotic training is combine with the admini-stration of quipazine [8].…”
Section: Introductionmentioning
confidence: 93%
“…However, fixed, repetitive training is very likely to be suboptimal, as variability is an intrinsic property of mammalian locomotion [5]. Hence, fixed locomotor training may lead to the phenomena of "learned helplessness" [6,7]. That is, the lower spinal cord becomes habituated to the training trajectory.…”
Section: Introductionmentioning
confidence: 99%